Fifteen years of Pseudo-nitzschia in an Australian estuary, including the first potentially toxic P. delicatissima bloom in the southern hemisphere. (5th May 2020) - Ajani, Penelope A.; Larsson, Michaela E.; Woodcock, Stephen; Rubio, Ana; Farrell, Hazel; Brett, Steve; Murray, Shauna A.
Abstract: In March 2018, an unprecedented bloom of a species of Pseudo-nitzschia occurred in Berowra Creek, a major tributary of the Hawkesbury River estuary, New South Wales, Australia (max cell abundance 5.7 × 10 6 cells L −1 ). Morphological and phylogenetic analysis showed the bloom was dominated by the species P. delicatissima, with toxin characterization by LC-MS confirming one of the seven strains isolated produced domoic acid (DA), at a concentration of 0.34 pg DA per cell. In response to this unprecedented bloom, we used a fifteen year series of phytoplankton and physico-chemical data to relate environmental factors to spatial and temporal variability of Pseudo-nitzschia species throughout the estuary. Species in the Pseudo-nitzschia delicatissima group consistently dominated all locations monitored throughout the estuary, with peak cell densities observed in the austral autumn (lowest in winter). Overall, Generalised Additive Models (GAMs) suggested that high cell concentrations of Pseudo-nitzschia were linked to an increase in soluble reactive phosphorus and a decrease in total nitrogen at all sites, with up to 55% of the deviance explained. Twenty species of Pseudo-nitzschia have now been reported in Australian coastal waters, four of which are confirmed DA producers. We hypothesise that increased urbanization, nutrient input and warmer waters could combine to increase Pseudo-nitzschia blooms in south-eastern Australia. Graphical abstract: Image 1 Highlights: Fifteen year study of Pseudo-nitzschia in a south eastern Australian estuary. a significantly large bloom occurred in March 2018. First reported bloom of P. delicatissima in the southern hemisphere. One of seven strains confirmed as producing domoic acid. GAMs suggested high cell concentrations were linked to soluble reactive phosphorus.